Tektonika Kayu pada Museum Wiswakarma Sebagai Kajian Bentuk Struktur dan Tampilan Estetika - I Wayan Angga Wiradana; Kadek Wahyu Kartika Putra; I Komang Mahendra Adi Wijaya; Cokorda Istri Arina Cipta Utari; I Gede Surya Darmawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
The structure is not only a construction element, but also can give birth to the aesthetics of the building. The beauty in these structures is called tectonics. The Wiswakarma Museum is a building that has beauty in its structure, so it has the potential to be explored using a tectonic approach. The tectonic concept applied using wood as the main material is called wood tectonics. Wood tectonics is a building construction system that uses wood materials and can produce an aesthetic appearance. The problem raised in this research is how to apply the concept of wood tectonic at the Wiswakarma Museum. This research was conducted with the aim of revealing the application of wood tectonics at the Wiswakarma Museum by paying attention to tectonic aspects (principle of stability, principle of strength/rigidity/rigid, principle of balance, principle of visual aesthetics of tectonic structures, and flow of load acceptance). This study uses a qualitative method that is descriptive or descriptive analysis that describes the tectonics of wood at the Wiswakarma Museum. The final result of this research is a study of wood tectonics at the Wiswakarma Museum so that later they can understand the tectonic aspects of the Wiswakarma Museum.